Núcleo ejecutor y la distribución descentralizada en los comedores populares de Lima Metropolitana 2017 - Camacho Caballero, César Igor (2018)
The present work of investigation was elaborated by the purpose of determining the solution to the raised problem: which is the incident of the executing core in the distribution decentralized in the popular dining rooms of the Metropolitan Lima 2017? With the determination of this work, the investigator will put emphasis in the raised hypothesis: The management of the executing core affects significantly in the distribution decentralized in the “popular dining rooms” of Metropolitan Lima 2017. For the present research report the design was in use descriptive - comparative, statistician; and one worked historic information of 22 pictures as technology of investigation historic information applied to the “popular dining rooms” of the bright green district metropolitan. We can highlight that the executing core affects significantly in the distribution decentralized in the “popular dining rooms” of the Metropolitan Lima 2017. As conclusion of the same one, the management of the executing core affects significantly in the distribution decentralized in the “popular dining rooms” of the Metropolitan Lima 2017. Show all the benefits that obtained the popular dining rooms.